O papel da concessão na construção do sentido e do efeito persuasivo no discurso publicitário : uma estratégia para o julgamento universal - Fernandez, Patrícia Nystrom (2013)
Aiming to persuade its public, advertising uses a series of strategies, among them the creative manipulation of the language which is used in advertisements. Bearing this in mind, we developed this study, with the hopes of demonstrating how meaning is built in advertising discourses, which have a double function: to communicate and to convince. Furthermore, we aim to highlight concession, while a linguistic phenomenon, as an effective persuasive tool, as well as explain the relevance of the interlocutor's projection so that the advertisement reaches its goal. Therefore, we based this work on theories which start from Plato's notion of alterity, include Saussure's concepts of language, speech and value, Benveniste's concept of empty signs and his studies on subjectivity and intersubjectivity, and arrive at the present days, with the studies of Oswald Ducrot and Marion Carel on building meaning and semantic blocks. Based on this theoretical analysis, we demonstrate how meaning is established in statements by argumentative chains and internal and external argumentation. Thereafter, we lay emphasis on the meaning generated by concession, which evokes a transgression of the norm, thus conducting the interlocutor to a universal and positive judgement about what is offered him. Consequently, our corpus is constituted of advertising pieces which are similar because they have concessive statements in their discourses. As a result, we intend to evidence how advertising language, which is deeply imbued with subjectivity and intentionality, uses linguistic resources to obtain the much desired persuasive effect.